(untitled) (Pakistan Journal of Medical & Cardiological Review, 2026)
Background: Lahore ranks as a highly populated metropolitan area in Pakistan, where tuberculosis is still a major health concern. Effective control measures depend on precise grassroots statistics on adults TB prevalence and corresponding risk factors. Objective(s): The purpose of this study is to determine the incidence of TB within adults in Lahore, Pakistan, as well as the clinical, psychological, and economical risk factors linked to the illness. Methodology: A cross-sectional study has been carried out with 78 adult volunteers who were selected from Mughal Labs and Diagnostic Center (n = 46) from Nawaz Sharif Social Security Teaching Hospital (n = 32) in Lahore. Data on the population, symptom (cough, fever, chest discomfort), and smoking habits were gathered using a standardized questionnaire. All individuals had their sample sputum taken, and GeneXpert MTB/RIF was used to screen for TB. Chi-square tests were used to examine the information utilizing SPSS version 25, with p<0.05 being deemed statistically meaningful. Results: Most participants were between the ages of 38 and 45 (52.6%, n = 41), accompanied by those between the ages of 28 and 37 (28.2%, n = 22) and 18 and 27 (19.2%, n = 15). There were 47.4% (n=37) females as well as 52.6% (n=41) men. To summarize, 65.4% (n=51) of people had TB. Chest discomfort was noted by 65.4% (n=51), fever by 69.2% (n=54), and coughs by 66.7% (n=52). 39.7% (n=31) admitted smoking. Age as well as TB status were shown to be statistical significantly correlated (p=0.030), resulting in the 38–45 age group having the greatest burden. Age did not significantly correlate with cough, fever, chest discomfort, or smoking. Conclusion: Adults in Lahore have a high prevalence of tuberculosis, and there is a strong correlation between disease and age. Programmes for specialized screening of older persons are desperately needed.